The influence of benzene air pollution on leukemia incidence and mortality rates - Pilarska, Agnieszka; Pospieszyńska, Aleksandra (Bulletin of Geography. Physical Geography Series, 2021)
The following study identifies areas where adverse conditions related to benzene pollution are concurrent with leukaemia incidence and mortality (C91-C95). Moreover, it determines the similarities between benzene and leukaemia levels, as well and rules defining their co-occurrence. The analysis covered the period of 2015-2017. Data was obtained from Dane.gov.pl (number of leukaemia cases), Polish National Cancer Registry website (number of deaths), Local Data Bank of the Central Statistical Office (population data) and from Chief Inspectorate of Environmental Protection and found via the Air Quality Portal (data on air quality). Based on the carried out analysis, it was concluded that areas with an unfavourable epidemic situation related to leukaemia are the following poviat towns: Kielce (incidence), Rzeszów (incidence), Elbląg (mortality), while high leukaemia incidence and mortality co-occur with high average benzene concentration in 2015 -2017 in the following poviat towns: Kielce, Rybnik, Płock and Rzeszów. It was found that leukaemias belonging to the following three-character ICD-10 categories: C94, C95 and C92, show the highest rate of co-occurrence with benzene concentration. In addition, two main rules for the co-occurrence of benzene pollution and leukaemia were identified. It was also noted that it is necessary to continue the research over a longer-period of time, especially in the following poviat towns: Kielce and Rzeszów.